The Fifa 100 - Pele. (London : Royal Academy of Arts, 2004)
Who does Pele think are the greatest footballers alive? This beautiful book, which celebrates FIFA's centenary, reveals his selection. These portraits, commissioned from some of the world's leading photographers, are surprising and unexpected. Unlike the familiar football books that are packed with action shots by anonymous news photographers, in The FIFA 100 the very essence of athletic greatness is depicted. These arresting portraits reveal the footballer as icon; strength and artistry of movement are implied. In The FIFA 100, art meets football, and the book is a fitting tribute to all the players who have made the game so beautiful. With forewords by Pele and Sepp Blatter, the President of FIFA, the book contains more than 100 stunning portraits and a biography of each player and photographer. It accompanies a touring exhibition of these pictures, which has been organised by FIFA for its centennial year.